Adding Sound Transparency to a Spacesuit: Effect on Cognitive Performance in Females - Jose Berengueres; Mariam AlKuwaiti; Mohamed Abduljabbar; Fatma Taher (IEEE Open Journal of Engineering in Medicine and Biology)
Spacesuits may block external sound. This induces sensory deprivation; a side effect is lower cognitive performance. This can increase the risk of an accident. This undesirable effect can be mitigated by designing suits with sound transparency. If the atmosphere is available, as on Mars, sound transparency can be realized by augmenting and processing external sounds. If no atmosphere is available, such as on the Moon, then an Earth-like sound can be re-created via generative AR techniques. We measure the effect of adding sound transparency in an Intra-Vehicular Activity suit by means of the Koh Block test. The results indicate that participants complete the test more quickly when wearing a suit with sound transparency.